2022
DOI: 10.30880/jtet.2022.14.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Challenges, Teaching Strategies and Personality Traits to Implementing an Effective Agriculture-Based TVET Program in South Africa

Abstract: Technical and Vocational Education and Training (TVET) is an educational field that emphasises on practical and lab-based learning environments. Equally important, TVET also makes a major contribution to the agriculture field. However, there are myriad issues that cause limited knowledge and skills for agricultural graduates, and these include butare not limited to the lack of resources, equipment, and infrastructure. The case study approach allows the in-depth collection of dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Badenhorst and Radile (2018) found that inadequate machinery, tools and equipment compel students to overcrowd machines during the practical training. Sephokgole et al (2022) also revealed that the lack of resources, equipment, and infrastructure has a negative implication on the provision of quality TVET programmes as lecturers are being prevented from exposing students adequately to hands-on practical skills. Therefore, effective teaching and learning is not stimulated due to the lack of machinery, equipment and tools for practical training.…”
Section: Provision Of Teaching and Learning Resources In Tvetmentioning
confidence: 99%
“…Badenhorst and Radile (2018) found that inadequate machinery, tools and equipment compel students to overcrowd machines during the practical training. Sephokgole et al (2022) also revealed that the lack of resources, equipment, and infrastructure has a negative implication on the provision of quality TVET programmes as lecturers are being prevented from exposing students adequately to hands-on practical skills. Therefore, effective teaching and learning is not stimulated due to the lack of machinery, equipment and tools for practical training.…”
Section: Provision Of Teaching and Learning Resources In Tvetmentioning
confidence: 99%
“…For example, a study by Nkwanyane (2023) reveal that the NCV: Building and Civil Engineering program is not aligned with the industry expectations and that the curriculum is too theoretical to the detriment of TVET students. Also, Ramongwane, Manto and Moses (2022) report that TVET colleges are still battling in balancing discipline specific teaching and learning resources, equipment, plus a responsive infrastructure for lecturers to impart practical knowledge and skills. Perhaps it is even fair to say that not much is known about relevant teaching methodologies and philosophies that underpin TVET college lecturers' andragogical and pedagogical activities.…”
Section: Introductionmentioning
confidence: 99%